2022
DOI: 10.3390/ani12162068
|View full text |Cite
|
Sign up to set email alerts
|

Refining the Camelus dromedarius Myostatin Gene Polymorphism through Worldwide Whole-Genome Sequencing

Abstract: Myostatin (MSTN) is a highly conserved negative regulator of skeletal muscle in mammals. Inactivating mutations results in a hyper-muscularity phenotype known as “double muscling” in several livestock and model species. In Camelus dromedarius, the gene structure organization and the sequence polymorphisms have been previously investigated, using Sanger and Next-Generation Sequencing technologies on a limited number of animals. Here, we carried out a follow-up study with the aim to further expand our knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
2
0
2
Order By: Relevance
“…Testosteron dan androgen lainnya juga berperan dalam mengatur myostatin, dengan penelitian yang menunjukkan bahwa pengebirian menyebabkan peningkatan ekspresi myostatin dan penurunan massa otot. Selain itu, ekspresi myostsatin diatur oleh berbagai jalur pensinyalan, termasuk jalur Smad, yang diaktifkan oleh pengikatan myostatin ke reseptornya, dan jalur Akt/mTOR, yang terlibat dalam sintesis protein otot (Bruno et al, 2022;Grade et al, 2019;Konovalova et al, 2021b).…”
Section: Dengan Menggunakan Sekuens Dari Ncbi Pada Spesiesunclassified
See 1 more Smart Citation
“…Testosteron dan androgen lainnya juga berperan dalam mengatur myostatin, dengan penelitian yang menunjukkan bahwa pengebirian menyebabkan peningkatan ekspresi myostatin dan penurunan massa otot. Selain itu, ekspresi myostsatin diatur oleh berbagai jalur pensinyalan, termasuk jalur Smad, yang diaktifkan oleh pengikatan myostatin ke reseptornya, dan jalur Akt/mTOR, yang terlibat dalam sintesis protein otot (Bruno et al, 2022;Grade et al, 2019;Konovalova et al, 2021b).…”
Section: Dengan Menggunakan Sekuens Dari Ncbi Pada Spesiesunclassified
“…Mutasi pada gen MSTN telah diidentifikasi pada pada Belgian Blue, Piedmontese, Aberdeen Angus, Limousin, dan Simmental. Secara nyata jika dilihat cattle dengan mutasi gen MSTN memiliki bentuk tubuh yang lebih kekar (Bi et al, 2020;Bruno et al, 2022;Grade et al, 2019). Seperti contoh, Mutasi nt821 (del11) dikaitkan dengan cacat genetik otot ganda pada Belgian Blue, sedangkan mutasi F94L telah terbukti memiliki efek aditif pada sifat karkas pada beberapa jenis cattle.…”
Section: Dengan Menggunakan Sekuens Dari Ncbi Pada Spesiesunclassified
“…Similar SNP (C/T) was found at positions 062 and 232, respectively in Nigerian indigenous camels ( Ibrahim et al, 2022 ). In a related study of the myostatin (MSTN) gene, which affects muscularity (Ramadan and Inoue-Murayama; Bruno et al, 2022 ) using twenty two camel samples from Tunisia, Algeria, and Egypt, Muzzachi et al (2015) found at intron 1, G486C, G798A and C799T substitutions. This could be a reflection of the peculiarity of the evolutionary history of camels in the three north African countries.…”
Section: Single Nucleotide Polymorphisms (Snps)mentioning
confidence: 99%
“…In the last decade, various GWAS studies have been undertaken on livestock, including socially affected traits and body mass index in Yorkshire pigs [32,33], coat color traits in Arab camels and cattle [34,35], meat quality in camels [36], foot and leg conformation traits in Chinese Holstein cattle [37], milk fatty acid traits in Comisana sheep [38], litter size in sheep [39], body weight traits in yaks [40], growth traits in Braunvieh cattle [41], and growth traits in broilers [42]. Whole-genome sequencing has been used to detect population structures and to identify polymorphisms that might affect the economic traits of livestock animals [43].…”
Section: Introductionmentioning
confidence: 99%